Effect of phytase dosage and source on growth performance of nursery pigs - B W James; G L Lynch; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
A 28-d growth assay was conducted to determine the effect of phytase dosage and source on growth performance of nursery pigs. The nine experimental treatments were control diets (0.13, 0.18, and 0.23% available phosphorus) and phytase (100, 225, or 350 FTU or FYT/kg) from either Natuphosï£¨ or Ronozymeï£ª P added to the 0.13% available P diet. The results of this experiment indicate that increasing available P or phytase level, through 0.23% available P and 350 FTU or FYT/kg, respectively, improves ADG and feed efficiency. Regression analysis of the ADG response indicated that, when adding less than 350 phytase units/kg, each 100 phytase units/kg will release 0.022 and 0.017% available P for Natuphosï£¨ and Ronozymeï£ª P, respectively.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Phytase; Phosphorus; Nursery pigs; Swine